Significance of TOPSIS approach to MADM in computing exponential divergence measures for pythagorean fuzzy sets - Arora, H.D.; Naithani, Anjali (Decision Making: Applications in Management and Engineering, 2022)
Managers nowadays face challenging decisions on daily basis and must weigh a growing number of factors while making such decisions. Previously, such judgments were frequently assessed solely based on a single criterion, such as profit or cost. Cost or profit, on the other hand, rarely captures the desirability of a decision option. One of the most common and popular research domains in decision science theory is the multiple attribute decision making (MADM) problem. To deal with such issues, a variety of approaches have been presented including TOPSIS. The primary goal is to uncover the importance aspect of divergence measures based on exponential function under Pythagorean fuzzy sets (PFSs), proposed by Yager (2013) and its application to multi attribute decision making. Numerical computations have been carried out to validate our proposed measures. Moreover, comparison of the result for the proposed measures has been carried out to demonstrate the efficacy.